INHIBITION OF BIFIDOBACTERIUM sp ISOLATED FROM INFANTS FECES TOWARDS ADHESION OF SALMONELLA TYPHI ON BALB/c MICE ENTEROCYTE - Sukrama, I D. M.; Sukardika, K.; -, Sumarno; Mantik Astawa, N. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2010)
Diarrhea, up to the recent year remains a cause of high morbidity and mortalityworldwide, especially in developing countries including Indonesia. Research concerning ofmanagement, prevention, and medication of the disease have been continually improved. Theaim of this research is searching Bifidobacterium sp isolated from infants feces. ThisBifidobacterium was then applied as an anti-adhesion of Salmonella typhi in the hope to gain acure of diarrhea. This research employed two research designs, namely descriptive explorationand true experimental. Exploration was applied in order to obtain isolation and characterizationof Bifidobacterium isolated from infants feces. Adherence ability of this Bifidobacterium sptowards Salmonella typhi adhesion on mice entherocyte was then carried out by applyingRandomized Posttest-Only Control Group Design. In this research, average Bifidobacterium spadhesion index of 1950 on entherocyte was obtained. In simple word, there are 19.5Bifidobacteria adhere to any single entherocyte cell. This adhesion index value is highercompare to Salmonella typhi adhesion of 1504. Conclusions that can be drawn from this researchare the finding of Bifidobacterium sp isolated from infants feces. This Bifidobacterium sp has anability to inhibit adhesion of Salmonella typhi on BALB/c mice enterocyte. Future work that canbe carried out are further researches concerning whether these bacteria have an ability to inhibitadherence of other pathogen bacteria. More over, searching of cell wall adhesin ofBifidobacterium sp that can be used as a replacement of life probiotic bacteria is also a greatinterest of research to be carried out.